Incidental findings detected on cone beam computed tomography in an older population for pre‐implant assessment. (18th June 2020) - Nguyen, P‐N; Kruger, E; Huang, T; Koong, B
Abstract: Objectives: The aim of this retrospective study was to record incidental findings in CBCT scans taken in an older population for pre‐implant assessment, and to examine whether these findings would influence the intended dental implant placement. Methods: 300 consecutive CBCT scans over the age of 40 years was carried out. The incidental findings were grouped into regions as follows: dentoalveolar structures, maxilla and mandible, paranasal sinuses, temporomandibular joint (TMJ), naso/oral‐pharyngeal airway, cervical spine and neurovascular canals. The incidental findings are further categories into their significance towards the intended treatment plan. Result: Incidental findings were noted on all of the scans. 555 incidental findings (1.85 findings/scan) were identified. The highest number of incidental findings was in the sinuses (34%), followed by dentoalveolar structures (31%), nasal/oral‐pharyngeal airway (12%), maxilla and mandible (10%), TMJ (6%), cervical spine (4%) and neurovascular canals (3%). A total of 37% of findings required follow‐up. In 12% of cases detection of the incidental findings lead to amendment or abortion of the intended implant treatment plan. Conclusion: Incidental findings within and beyond the region of interest are common in CBCT scans. The numbers of incidental findings per scan in an older population is higher than in a younger population.